1992
DOI: 10.1042/bj2810657
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a new galactanase from Penicillium oxalicum catalysing the hydrolysis of β-(1→5)-galactofuran linkages

Abstract: An endo beta-(1----5)-galactofuranase from Penicillium oxalicum has been purified 91-fold. The enzyme is a basic glycoprotein with a pI 7.9 and 20% (w/w) carbohydrate content, galactose being the principal sugar. The apparent Mr of the enzyme estimated by denaturing gel electrophoresis was 77,000. The optimum pH was 5.0, and the enzyme was stable over the pH range 4.0-7.5. This enzyme hydrolyses specifically (1----5)-linked beta-D-galactofuranose residues in homo- and heterogalactans, but did not hydrolyse o-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Enzymatic hydrolysis of 1(1-5)-linked galactofuranosyl residues from EPS of P. charlesii by an exo-13-D-galactofuranosidase produced by this fungus was reported (26). An endo-13(1-5)-D-galactofuranosidase from P. oxalicum and the enzymatic hydrolysis of 13(1-5)-galactofuranosyl residues from polysaccharides obtained from Eupenicillium crustaceum and Talaromyces flavus have also been reported (25). However, the influence of the exo-13-D-galactofuranosidase on the antigenic properties of EPS has not been studied.…”
mentioning
confidence: 99%
“…Enzymatic hydrolysis of 1(1-5)-linked galactofuranosyl residues from EPS of P. charlesii by an exo-13-D-galactofuranosidase produced by this fungus was reported (26). An endo-13(1-5)-D-galactofuranosidase from P. oxalicum and the enzymatic hydrolysis of 13(1-5)-galactofuranosyl residues from polysaccharides obtained from Eupenicillium crustaceum and Talaromyces flavus have also been reported (25). However, the influence of the exo-13-D-galactofuranosidase on the antigenic properties of EPS has not been studied.…”
mentioning
confidence: 99%
“…Cell wall-degrading enzymes, such as chitinase and glucanase (Mavingui and Heulin 1994;Nielsen and Sorensen 1997), are capable of distorting hyphal cells and egg shells. Therefore, chitinase could also play a role in causing nematode mortality because it has been reported that P. oxalicum (ATCC number 201888) also produces chitinase (Rodriguez et al 1993), galactanase (Reyes et al 1992) and b-N-acetylglucosaminidase . It has also been reported that the chitinase from Paenibacillus illinoisis KJA-424 causes lysis of the Meloidogyne incognita eggshell, as well as inhibiting juveniles hatching and causing abnormal swelling and deformation of Rhizoctonia solani hyphae (Jung et al 2002(Jung et al , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides from Talaromyces flavus,7) Talaromyces wortmanii, 8) and Eupenicillium crustaceum 9 ) were provided by Dr. J. A. Leal, Centro de Investigationes Biologicas, CSIC, Madrid, Spain.…”
Section: Methodsmentioning
confidence: 99%
“…3) The enzyme did not cleave 13(1 ~ 2) and/or f3(l ~ 3) linkages of galactofuranoside residues of T. wortman ii, 8) galactomann an of S. pombe or the galactopyranosyl linkages present in gum arabic, gum ghati, gum guar, arabi no galactan, araban, and pectic acid. The column (4.6 x 250 mm) was eluted with two solvents as described under Materials and Methods.…”
Section: Galactofuranosidase Action On Polysaccharide Containing Galamentioning
confidence: 99%